Background Knowledge and the Construction of a Situational Representation from a Diagram - Lowe, Richard K (European journal of psychology of education, 1996)
Shows that the construction of mental representations that capture a situation based on the comprehension of a diagram are mediated by the possession of appropriate background knowledge. Indicates that background knowledge deficiencies may make it difficult for beginning students of a domain to construct suitable mental representations from domain-related diagrams. (DSK)